The felt needs assessment of a typical public Library in the Information age: the case of Osun of Osun state branch of the National Library of Nigeria (2011)
This study addressed the felt needs of the library users at National Library of Nigeria (NLN), Oshogbo, in an attempt to determine the extent of user satisfaction and the provision of improved library services in and around Oshogbo, Osun State. Copies of as self administered "library needs assessment" questionnaire were admistered to 120 library clinetele over a period of two weeks. Ninety two copies of the questionnaire were duly completed and returned for analysis. The result showed that majority of the correspondents were students. Highest on their list of felt needs was the provision of more reading space 67(72.8%), while only 13 (14.1%) users felt that the provision of the internet connectivity was a major priority. Only 3 (3.3%) respondents were satisfied with the library resources provided at the National Library of Nigerian (NLN) Oshogbo. Majority of the respondents 67(72.8%) were satisfied with the performance of the library staff. Apart from the provision of a quiet reading room as indicated by 57(62.0%), 41(44.6%) respondents requested for the provision of a computer training center. In conclusion, the finding of the study suggest that Osun branch of NLN, Oshogbo has great potentials but with major financial constraints. The facilities need to be enlarged and upgraded with the provision of a computer training center, Internet connectivity and computer work stations